Structural dynamic analysis of vertical bars of turbine protection trashracks of hydroelectric plant - Giovanetti, Lucas [UNESP]; De Souza Soares, Álvaro Manoel [UNESP]; Chaves, Carlos Alberto [UNESP] (Corporacion Universitaria Remington, 2016)
Trashracks of hydroelectric plants are very important equipment because they are responsible for protection of hydraulic turbines against impact of floating bodies. These structures are basically constituted by horizontal beams and vertical bars that are subjected to action of dynamic loads resulting from flow of water. Objective of this study is to analyze vertical bars of trashracks subjected to action of water flow. In other words, to analyze the responses of structure, and the behavior of water flow, using the calculations of structures dynamics coupled with computational fluid dynamics techniques (CFD). For execution of these analyzes, is utilized the commercial software CFX version 14. These results calculated are the stresses, displacements of the vertical bars, and the profile of velocities of flow. Considering the model proposed, seven analyzes are executed with different values of speeds in order to compare the numerical data calculated by the software with values experimentally obtained. Finally, a modal analysis of a vertical bar is shown in order to verify the results.
Keywords: Computational fluid dynamics; Fluid-Structure interaction; Trashracks; Turbulent flow